PENGARUH CAPITAL INTENSITY, CORPORATE SOCIAL RESPONSIBILITY, DAN ENVIRONMENTAL UNCERTAINTY TERHADAP TAX AVOIDANCE - Muhammad Daffa Wardhana, - (2021)
This research is using quantitative study that aims to investigate the effect of capital intensity, corporate social responsibility, and environmental uncertainty on tax avoidance. Tax avoidance in this study uses the Abnormal Book Tax Difference (ABTD) measurement. The sample of this research was 138 manufacturing companies listed on the Indonesia Listed Exchange in the 2016-2018 period. The analysis technique used is multiple regression analysis with panel data using STATA program. The results indicated that (1)capital intensity has no significant effect on tax avoidance (2)corporate social responsibility has significant effect on tax avoidance (3)environmental uncertainty has no significant effect on tax avoidance. The results of this study explain that disclosure of high corporate social responsibility can reduce tax avoidance. So this research can help investors in understanding the factors that companies do in tax avoidance.